Antidepressants and Psychological Treatment: Hard Reasons for Synergy - Campagne, Daniel M. (Revista de Psicopatología y Psicología Clínica, 2021)
Abstract: Improving the efficacy of depression treatment is a clinical necessity. «Synergy» is the systematic process in which different treatments of and approaches to mood disorders are evaluated and made to work coherently to optimize their results. Depression treatment has shown to benefit from the synergy of pharmacological and psychological processes. Our aim was to evaluate present evidence as to synergizing psychological therapy and pharmacotherapy in mood disorders, reflecting the related brain systems and circulating biological substances. Multiple brain regions are involved in mood disorders, resulting in multiple-target effects of substances, each influencing neurobiological balance, and depending on individual aspects. Large studies showed that psychological treatment may, overall, be more effective than medication. However, the synergy of both provided significantly increased effects that were largely independent of each other, and each added about 50% to the overall effects of combined treatment. Identified neuropsychobiological pathways were found, as well as appreciable evidence that, in depression, the synergy of both treatments can be expected to produce better results through reciprocal effects in cortical, subcortical and visceral systems. In compromised situations such as pregnancy and adolescence, psychological treatments for mood disorders may have preference over drug treatment, but synergy remains essential. Keywords: Depression; mood disorders; neurobiology; pharmacotherapy; psychological treatment; synergy Antidepresivos y tratamiento psicológico: Razones contundentes para la sinergia Resumen: Mejorar la eficacia del tratamiento de la depresión es una necesidad clínica. «Sinergia» es el procedimiento sistemático que evalúa y hace funcionar coherentemente tratamientos y/o enfoques sobre trastornos de ánimo diferentes para optimizar los resultados. El tratamiento de la depresión ha demostrado beneficiarse de la sinergia de procedimientos farmacológicos y psicológicos. Nuestra meta era evaluar la evidencia existente en cuanto sinergias entre la terapia psicológica y la farmacoterapia en los trastornos de ánimo, reflejando los sistemas cerebrales y las sustancias biológicas circulantes. Trastornos de ánimo involucran múltiples regiones del cerebro, resultando en efectos de los fármacos sobre múltiples metas, cada una influyendo el equilibrio neurobiológico, dependiendo de los aspectos individuales. Amplios estudios demuestran que, generalmente, el tratamiento psicológico puede ser más eficaz que los antidepresivos. Sin embargo, la sinergia de ambos produjo efectos significativamente mayores y en gran medida independientes, aportando ambos aproximadamente un 50% a los efectos totales del tratamiento combinado. Encontramos vías sinérgicas neuropsicobiológicas identificadas. Consta evidencia apreciable que, en depresión, es de esperar que la sinergia de ambos tipos de tratamientos produzca mejores resultados por sus efectos recíprocos en sistemas corticales, subcorticales y viscerales. En situaciones comprometidas, tales como el embarazo y la adolescencia, los tratamientos psicológicos de los trastornos de ánimo pueden merecer preferencia sobre el tratamiento con fármacos, pero sinergia sigue siendo esencial. Palabras clave: Depresión; trastornos del estado de ánimo; neurobiología; farmacoterapia; tratamiento psicológico; sinergia